Chiral separation of vinpocetine using cyclodextrin-modified micellar electrokinetic chromatography - Wan Ibrahim, Wan Aini (Wiley Periodicals, Inc, 2012)
A cyclodextrin-modified micellar electrokinetic chromatography (CD-MEKC) technique has been developed for enantioseparation of vinpocetine using an inexpensive 2-hydroxypropyl-β-CD (HP-β-CD) as the chiral selector (CS). The best chiral separation was achieved using 40 mM HP-β-CD as the CS in 50 mM phosphate buffer (pH 7.0) consisting of 40 mM sodium dodecyl sulfate (SDS) at a separation temperature and separation voltage of 25°C and 25 kV, respectively. To the author's best knowledge, this is the first CD-MEKC study able to successfully separate the four stereoisomer of vinpocetine in separation time of 9.5 min and resolution of 1.04-3.87. Chirality, 2012. © 2012 Wiley Periodicals, Inc.